SISTEM INFORMASI AKUNTANSI PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI PENENTU HARGA JUAL DENGAN METODE JOB ORDER COSTING BERBASIS WEB STUDI KASUS DI PT SEMERU KARYA BUANA - Restia Nur Rachmawati; Sumaryanto Sumaryanto (Universitas Sains dan Teknologi Komputer, 2018)
Calculation of Cost of Production is one of the important aspects in carrying out business activities. Cost of Production is one of the determinants of the selling price of a product. Besides the cost of production can indicate a company's profit. But the activity of recording the cost of production at PT Semeru Karya Buana still uses a manual method that is using excel. This causes ineffectiveness in time, the resulting information will take longer because they have to look for the components one by one. Not to mention the data generated is most likely an error in the calculation. This research is intended to study the system that is already running. And later it will produce a program to calculate the cost of production as a determinant of the selling price which is implemented with the PHP programming language and MYSQL database. The calculation method uses the Job Order Costing Method where the price of the product to be given to consumers is calculated by dividing all costs incurred to produce a product by the number of orders. So the benefits of each product can be directly calculated. The more accurate the data produced, the better the company is in carrying out the buying and selling process.